Status Jurídico-Constitucional de las Lenguas Indígenas en América Latina - Irarrázabal, César Cisternas (Diálogos Latinoamericanos, 2015)
The constitution is the fundamental norm that rules the modern Nation-States. Consequently, what it is stipulated in it gives an idea of the relevance that the incorporated (or not incorporated) elements have to the State. The present research analyses the juridicalconstitutional status of the indigenous languages in the countries of Latin America, from the perspective of the sociology of language. The method chosen is the content analysis of the constitutional articles referring to language and the nature of the Nation-State. It has been found that only seven countries (mainly from the Andean region of Southern America) have declared official the vernacular languages, which implies that a 60.5% of the indigenous people from the subcontinent dwells in countries in which it has not been given that character to their ancestral languages.